Introducing SDL Trados to Beginning Translators - Kurniawati, Lemmuela Alvita; Rahajeng, Dian Titi; Kristianto, Barlian; Kastuhandani, Fidelis Chosa (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2016)
Over years, translators have been incorporating new advances in technology into their work. A number of attempts in developing ideal translator’s workstations usingtechnology have been made, one of such stations is a Computer-Aided Translation(CAT) tool. CAT tools facilitate translators to increase their productivity and efficiencyby providing them with some utilities, such as a Translation Memory and an AlignmentTool to support their translation works. This article highlights the usefulness of SDLTrados 2014, as one of the most widely used paid CAT tools, in translating the textsmore effectively and in a timely manner. Further, it describes the basic steps in usingSDL Trados and exemplifies SDL Trados 2014 translation results. A sample text wastranslated from Indonesian to English using both Across (a free CAT tool) and SDLTrados (a paid CAT tool). Eventually, the results of translating using both CAT toolsappear to prove that SDL Trados helps the translators to translate more consistently,accurately, effectively and in a timely-manner. Keywords: CAT tools, SDL Trados, Across.